Eastern Visayas State University (EVSU) Registrar: e-Assist System - Macion, Ma. Jezabelle; Brosas, Deborah; Codilan, Vinceloyd (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated the EVSU Registrar: e-Assist System to improve service efficiency, accessibility, and client satisfaction within the Registrar’s Office of Eastern Visayas State University. Guided by the Input–Process–Output framework and supported by Natural Language Processing (NLP)-based chatbot technology, the system integrated online document requests, real-time transaction tracking, appointment scheduling, automated notifications, customer feedback collection, reports and analytics, FAQs, and chatbot assistance. A mixed-methods research design was employed, combining qualitative and quantitative approaches. Data were gathered through interviews, surveys, structured questionnaires, and system evaluations involving students, alumni, registrar personnel, and ICT personnel. Qualitative data were analyzed using thematic analysis, while quantitative data were evaluated using the ISO/IEC 25010 Software Quality Model. The findings revealed four major challenges affecting registrar operations: operational constraints and resource limitations, inefficient manual processes and records management, information accessibility concerns, and the increasing demand for service automation. The developed system addressed these issues by providing accessible self-service functionalities and improving information dissemination and transaction management. Evaluation results showed excellent performance across functionality, reliability, usability, efficiency, maintainability, portability, and security, with an overall weighted mean score of 4.74, indicating high user satisfaction and software quality. The study concluded that the EVSU Registrar: e-Assist System effectively enhanced service delivery, reduced reliance on manual processes, and supported data-driven decision-making. It is recommended that the system be implemented and continuously improved through user feedback, regular monitoring, and periodic updates. The study supports Sustainable Development Goal (SDG) 4 by improving access to educational services, SDG 9 through the adoption of innovative digital technologies, and SDG 16 by promoting transparency, accountability, and efficient institutional services. Its sustainability impact lies in strengthening institutional efficiency, technological modernization, and continuous quality improvement within higher education service delivery.